(untitled) - MacIntyre, Alasdair (Notre Dame, Indiana, 1984)
Morality, according to Alasdair MacIntyre, is not what it used to be. In the Aristotelian tradition of ancient Greece and medieval Europe, morality enabled the transformation from untutored human nature as it happened to be to human nature as it could be if it realized its telos (fundamental goal). Eventually, belief in Aristotelian teleology waned, leaving the idea of imperfect human nature in conflict with the perfectionist aims of morality. The conflict dooms to failure any attempt to justify the claims of morality, whether based on emotion, such as Hume's was, or on reason, as in the case of Kant. The result is that moral discourse and practice in the contemporary world is hollow: although the language and appearance of morality remains, the substance is no longer there. Disagreements on moral matters appeal to incommensurable values and so are interminable; the only use of moral language is manipulative.
Keywords: Ethics,Virtues,Virtue